Application of Overall Index of Pollution (OIP) for the Evaluating of the Water Quality in Al-Gharraf River southern of Iraq - Al-Mayah, Wisam Thamer; Rabee, Adel M. (Iraqi Journal of Science, 2018)
This comprehensive study investigates has been made to assess the water quality of Al-Gharraf River, which considered the main branch of Tigris River south of Iraq using the overall Index of Pollution (OIP), depending on 9 physical, chemical, and biological important parameters of water quality were analyzed: hydrogen ion concentration (pH), turbidity (NTU), total dissolved solid (TDS), dissolved oxygen (DO), biological oxygen demand (BOD5) , total hardness (TH), sulfate (SO4), nitrate (NO3),and fecal coliform (FC), which measured monthly at twenty one stations on the river during 2016-2017. Water quality deterioration has occurred in the last ten stations, consequently, the health status of the river has changed from acceptable to heavily polluted, and the fecal coliform bacteria (FC) was the major factor that affects the quality of the wter river. In this paper concluded that the Al-Gharraf River was in class poor and the Al-Gharraf River water is relatively not suitable for direct public usage in all seasons.